Autoantigens in the trabecular meshwork and glaucoma‐specific alterations in the natural autoantibody repertoire. Issue 3 (29th February 2020) - Beutgen, Vanessa M; Schmelter, Carsten; Pfeiffer, Norbert; Grus, Franz H
Abstract: Objectives: Primary open‐angle glaucoma (POAG) is a neurodegenerative disorder leading to a gradual vision loss caused by progressive damage to the optic nerve. Immunological processes are proposed to be involved in POAG pathogenesis. Altered serological autoantibody levels have been frequently reported, but complete analyses of the natural autoantibodies with respect to disease‐related alterations are scarce. Here, we provide an explorative analysis of pathways and biological processes that may involve naturally immunogenic proteins and highlight POAG‐specific alterations. Methods: Mass spectrometry‐based antibody‐mediated identification of autoantigens (MS‐AMIDA) was carried out in healthy and glaucomatous trabecular meshwork (TM) cell lines, using antibody pools purified from serum samples of 30 POAG patients and 30 non‐glaucomatous subjects. Selected antigens were validated by protein microarray ( n = 120). Bioinformatic assessment of identified autoantigens, including Gene Ontology (GO) enrichment analysis and protein–protein interaction networks, was applied. Results: Overall, we identified 106 potential autoantigens [false discovery rate (FDR) < 0.01], from which we considered 66 as physiological targets of natural autoantibodies. Twenty‐one autoantigens appeared to be related to POAG. Bioinformatic analysis revealed that the platelet‐derived growth factor receptor beta (PDGFRB) pathway involved in TM fibrosis was particularly rich in POAG‐related antigens. Antibodies to threonine‐tRNA ligase (TARS), component 1 Q subcomponent‐binding protein (C1QBP) and paraneoplastic antigen Ma2 (PNMA2) showed significantly ( P < 0.05) higher levels in POAG patients as validated by protein microarray. Conclusion: This study provides new insights into autoimmunity in health and glaucoma. Bioinformatic analysis of POAG‐related autoantigens showed a strong association with the PDGFRB pathway and also increased levels of PNMA2, TARS, and C1QBP autoantibodies in the serum of POAG patients as potential glaucoma biomarkers. Abstract : In this study, we identified 66 potential antigens in the trabecular meshwork (TM) as targets of natural autoimmunity. Of these antigens, 21 can be assigned a connection to primary open‐angle glaucoma (POAG). The platelet‐derived growth factor receptor beta (PDGFRB) pathway involved in TM fibrosis is especially represented by POAG‐related antigens.